Democracy in Bangladesh : political dimensions of national development : selected papers from the 2008 and 2009 conferences on Bangladesh at Harvard University - Khan, Zillur R. (Zillur Rahman), 1938-; Andaleeb, Dr. Syed Saad.; John F. Kennedy School of Government; Bangladesh Development Initiative; Democracy and Development in Bangladesh Forum (Boston, Mass.); Ash Institute for Democratic Governance and Innovation (Dhaka : University Press Limited, 2011)
Contributed papers presented at the conferences organized by Bangladesh Development Initiative along with Democracy and Development in Bangladesh Forum and The Ash Institute for Democratic Governance & Innovation, held at John F. Kennedy School of Government at Harvard University.
Includes bibliographical references and index.
GenEd
Keywords: Democracy -- Bangladesh -- Congresses; Bangladesh -- Politics and government -- Congresses